First seizure presentations in adults: beyond assessment and treatment. Issue 9 (4th April 2019) - Foster, Emma; Carney, Patrick; Liew, Danny; Ademi, Zanfina; O'Brien, Terry; Kwan, Patrick
Abstract : Almost 10% of people will experience at least one seizure over a lifetime. Although common, first seizures are serious events and warrant careful assessment and management. First seizures may be provoked by acute or remote symptomatic factors including life-threatening metabolic derangements, drug toxicity or structural brain lesions. An unprovoked first seizure may herald the onset of epilepsy and may be accompanied by medical and psychiatric illnesses. Accidents, injuries and death associated with first seizures are likely under-reported. The cognitive and emotional impact of first seizures is often neglected. Evaluation of a patient presenting with a first seizure requires careful history-taking and early specialist assessment, however optimal management strategies have not been extensively investigated. Further, advances in technology and the role of eHealth interventions such as telemedicine may be of value in the care of patients who have experienced a first seizure. This article reviews the impact and implications of first seizures beyond the scope provided in current guidelines which tend to focus on assessment and management. It examines the effect of first seizures on the well-being of patients; assesses morbidity and premature mortality in first seizures and discusses current and future directions to optimise safety and health of people with first seizures, with a focus on adult patients. Recognition of these issues is essential to provide adequate care for people with first seizures.